HAEMATOBIOCHEMICAL PROFILE OF BROILERS SUPPLEMENTED WITH WITHANIA SOMNIFERA (ASHWAGANDHA) AND ANDROGRAPHIS PANICULATA ( BHUINEEM). - Dhenge , S A; Shirbhate, R N; Bahiram , K B; Wankar , A K; Khandait , V N; Patankar, R B (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A study was conducted on broiler chicks to see the effect of Ashwagandha (Withania somnifera) root powder and Bhuineem (Andrographis paniculata) leaves powder on haematobiochemical profile. The supplementation of Ashwagandha alone in T1 group and Ashwagandha with Bhuineem in T3 group of broilers significantly increased haemoglobin concentration, total erythrocyte count, total leucocyte count and lymphocyte count as compared with control . The supplementation of Bhuineem in T2 group caused significant increase in haemoglobin concentration, total leucocyte count, lymphocyte count, and non significant increase in total erythrocyte, heterophil and monocyte counts as compared with control (T0) group. Eosinophil count decreased significantly and basophil count decreased non-significantly in all treatment groups as compared to that of control (T0) group. The supplementation Ashwagandha alone in T1 group and with Bhuineem in T3 of broilers effected significant increase in total serum protein and serum globulin level, non-significant increase in serum albumin level and significant decrease in A/G ratio of broilers as compared to that of control (T0) group. Group T2 showed significant increase in total serum protein and non significant increase in serum albumin and globulin levels and non significant decrease in A/G ratio as compared to that of control (T0) group of broilers.